2022
DOI: 10.3168/jds.2021-21581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymerized goat milk whey protein on physicochemical properties and microstructure of recombined goat milk yogurt

Abstract: Goat milk whey protein concentrates were manufactured by microfiltration (MF) and ultrafiltration (UF). When MF retentate blended with cream, which could be used as a starting material in yogurt making. The objective of this study was to prepare goat milk whey protein concentrates by membrane separation technology and to investigate the effects of polymerized goat milk whey protein (PGWP) on the physicochemical properties and microstructure of recombined goat milk yogurt. A 3-stage MF study was conducted to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…The desirable textural attributes of yogurt are high viscosity, smoothness, and thickness. Yogurt prepared from goat milk possesses a soft body, lower viscosity, and reduced water‐holding capacity (Tian et al ., 2022). This is majorly due to differences in casein content of goat milk (Tian et al ., 2022).…”
Section: Technological Challenges and Strategies To Overcome Problems...mentioning
confidence: 99%
See 2 more Smart Citations
“…The desirable textural attributes of yogurt are high viscosity, smoothness, and thickness. Yogurt prepared from goat milk possesses a soft body, lower viscosity, and reduced water‐holding capacity (Tian et al ., 2022). This is majorly due to differences in casein content of goat milk (Tian et al ., 2022).…”
Section: Technological Challenges and Strategies To Overcome Problems...mentioning
confidence: 99%
“…Yogurt prepared from goat milk possesses a soft body, lower viscosity, and reduced water‐holding capacity (Tian et al ., 2022). This is majorly due to differences in casein content of goat milk (Tian et al ., 2022). Goat milk has a lower concentration of α s1 ‐casein, which plays a pivotal role in the formation of firm gel, coagulum, and denser network of fermented dairy products, resulting in weak texture of goat milk yogurt.…”
Section: Technological Challenges and Strategies To Overcome Problems...mentioning
confidence: 99%
See 1 more Smart Citation
“…Organoleptic evaluation showed that encapsulation in general can increase customer satisfaction. It can be argued that masking the color and taste of microalgae by microencapsulation can be used to enrich dairy products with microalgae [10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…So, for example, an interesting direction is the preparation of whey protein concentrates from goat's milk. The concentrates were produced by membrane separation and the study of the effect of polymerized whey protein of goat milk on the physicochemical properties and microstructure of recombined goat milk yogurt [16]. The results indicated that polymerized whey protein made directly from raw milk could be a novel protein-based thickener for natural goat milk yogurt.…”
Section: Introductionmentioning
confidence: 99%